Media and Sport – Can Thez be Independent from each other - Ilić, Jelena R; Stanković, Veroljub S.; Živanović, Nenad M (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Only recently have people started to insist on professionalism in sport, and as a result sport is becoming a very successful media business – commercial activity on which very complex industrial endeavors are based. Sport itself, especially the Olympic Games, except for games and fun and high goals of bringing people together since ancient times, is beginning to represent a kind of job for many people, a primary activity which directly enables them not only to earn a living, but to make a profit as well. Thus, the very term ‘sports career’ becomes a general one, and the mere participation in sport becomes a profession just like any other. That is how ‘transfers’ and sponsorship deals today are worth millions, and minutes of advertisements during the broadcast of a match are becoming more and more expensive, and more and more money is being set aside for the rights to broadcast matches, for exclusive footage and pictures of famous athletes. An athlete is becoming a ‘brand name’, and companies through sponsorship deals and advertisements buy the right to the athlete: he becomes a synonym for values which should be imposed on the public and a message which should be sent to as many people as possible. Lately, this trend has expanded to include sports competitions. Major sports events are becoming the subject of geo-political and economic interest, and thus represent a field in which there is a clash between national identity and economic globalism. In such circumstances, a strong bond is forged between sport and the media, which reflects the current state in society. The question that imposes itself is: have we already crossed that critical point in which the industry of sport wins over the sports industry?